2022
DOI: 10.1155/2022/4599676
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-196-5p Promotes Proliferation and Migration in Cholangiocarcinoma via HAND1/Wnt/β-Catenin Signaling Pathway

Abstract: Accumulating evidence has indicated the crucial role of microRNA-196 in mediating tumor progression, while its significance in cholangiocarcinoma (CCA) remains unclear. In this study, we provided the first evidence that the expression level of miR-196-5p is elevated in both CCA cell lines and clinic specimen. MiR-196-5p inhibition notably suppressed cell proliferation as well as metastasis in CCA cell line HuCCT1. Furthermore, the interaction between miR-196-5p and its downstream molecule HAND1 was verified. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Although miR-205-5p has diverse effects in different malignancies, it is not known how it affects on CCA. The roles of other miRNAs in CCA have been reported previously: there is upregulation of miR-181b-5p 22 and miR-23a-3p 23 in human CCA tissues and of miR-196-5p in CCA cell lines 24 . On the other hand, miRNA-206 is downregulated in CCA cell lines 25 , miR-7-5p in intrahepatic CCA tissue and cell lines 26 , and miR-451 in human tissues and serum 27 in CCA patients compared with normal subjects.…”
Section: Introductionmentioning
confidence: 59%
“…Although miR-205-5p has diverse effects in different malignancies, it is not known how it affects on CCA. The roles of other miRNAs in CCA have been reported previously: there is upregulation of miR-181b-5p 22 and miR-23a-3p 23 in human CCA tissues and of miR-196-5p in CCA cell lines 24 . On the other hand, miRNA-206 is downregulated in CCA cell lines 25 , miR-7-5p in intrahepatic CCA tissue and cell lines 26 , and miR-451 in human tissues and serum 27 in CCA patients compared with normal subjects.…”
Section: Introductionmentioning
confidence: 59%
“…The miR-196-5p can boost cell proliferation and migration in ICC pathogenesis via HAND1/Wnt/β-catenin signaling pathway 18 . These results demonstrated that miRNAs as important regulatory non-coding RNAs played pivotal roles in the progress and pathogenesis 19 . However, there are fewer reports to insight into the regulatory miRNA–mRNA networks in ICC pathogenesis.…”
Section: Introductionmentioning
confidence: 82%